92.0k views
4 votes
Helpppp Plsssss!!! Thanks

Helpppp Plsssss!!! Thanks-example-1

2 Answers

2 votes

Answer:

B.
-5x(x^(2) +2x+3)


Explanation:


-5x^(3) -10x^(2) -15x

Apply exponent rule


-5x^(2) x-10xx-15x

Rewrite 15 as 5*3

Rewrite 10 as 5*2

=
5x^(2) x-5*2xx-5*3x

Factor out common term -5x

=
-5x(x^(2) +2x+3)


User Slinden
by
5.1k points
5 votes

Answer:

It's B

Explanation:

-5x(x^2)=-5x^3

-5x(2x)= -10x^2

-5x(3)= -15x^2

All together: -5x^3 - 10x^2 - 15x

User Angle
by
5.6k points